2023
DOI: 10.3390/genes14040836
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Environmental Stressors and DNA Methylation Levels in Placenta and Peripheral Tissues of Mothers and Neonates Evaluated by Applying Artificial Neural Networks

Abstract: Exposure to environmental stressors during pregnancy plays an important role in influencing subsequent susceptibility to certain chronic diseases through the modulation of epigenetic mechanisms, including DNA methylation. Our aim was to explore the connections between environmental exposures during gestation with DNA methylation of placental cells, maternal and neonatal buccal cells by applying artificial neural networks (ANNs). A total of 28 mother–infant pairs were enrolled. Data on gestational exposure to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…We refer to [73 ▪▪ ,123] for recent overviews. We cite recent reviews addressing these complex, multifacted processes involving: mother-fetus-placenta unit [78]; HPA axis and cortisol [120,124 ▪ ,125]; autonomic nervous system [125]; iron deficiency [126]; maternal inflammation and offspring microglial activity [127]; mitochondria [128]; microbiome [10,129–131]; maternal metabolic risk factors including diabetes, obesity, undernutrition, specific macro- and micronutrient intake (e.g., long-chain polyunsaturated fatty acids (PUFAs) [132–135]; epigenetic changes, epigenome wide associations studies, relevant for e.g., the HPA axis or oxytocin system [136] including DNA methylation, histone modification, microRNA and other-non coding RNA [73 ▪▪ ,135,137–139] or multiomics data (transcriptomics, proteomics, metabolomics, and microbiomics [140]); telomere length [57]; paternal mediated effects [141,142]; oxidative stress [143], breast milk composition [78]; oxytocin system [73 ▪▪ ]; serotonin functions (e.g., SCL6A4) [73 ▪▪ ]; brain-derived neurotrophic factor (BDNF) [73 ▪▪ ]; structural and functional brain alterations beyond regions previously identified as relevant (i.e., prefrontal cortex, hippocampus, amygdala (limbic system)) additionally including basal ganglia, anterior cingulate cortex, thalamus, middle and superior frontal gyri, occipital gyrus and precentral gyrus [9,31,108].…”
Section: Perinatal Mental Health and Offspring Outcome: Results Mecha...mentioning
confidence: 99%
“…We refer to [73 ▪▪ ,123] for recent overviews. We cite recent reviews addressing these complex, multifacted processes involving: mother-fetus-placenta unit [78]; HPA axis and cortisol [120,124 ▪ ,125]; autonomic nervous system [125]; iron deficiency [126]; maternal inflammation and offspring microglial activity [127]; mitochondria [128]; microbiome [10,129–131]; maternal metabolic risk factors including diabetes, obesity, undernutrition, specific macro- and micronutrient intake (e.g., long-chain polyunsaturated fatty acids (PUFAs) [132–135]; epigenetic changes, epigenome wide associations studies, relevant for e.g., the HPA axis or oxytocin system [136] including DNA methylation, histone modification, microRNA and other-non coding RNA [73 ▪▪ ,135,137–139] or multiomics data (transcriptomics, proteomics, metabolomics, and microbiomics [140]); telomere length [57]; paternal mediated effects [141,142]; oxidative stress [143], breast milk composition [78]; oxytocin system [73 ▪▪ ]; serotonin functions (e.g., SCL6A4) [73 ▪▪ ]; brain-derived neurotrophic factor (BDNF) [73 ▪▪ ]; structural and functional brain alterations beyond regions previously identified as relevant (i.e., prefrontal cortex, hippocampus, amygdala (limbic system)) additionally including basal ganglia, anterior cingulate cortex, thalamus, middle and superior frontal gyri, occipital gyrus and precentral gyrus [9,31,108].…”
Section: Perinatal Mental Health and Offspring Outcome: Results Mecha...mentioning
confidence: 99%
“…Additionally, deficiencies of micronutrients in pregnant mother rats, such as calcium, zinc and vitamin D, are linked to offspring MetS ( 22 ). Furthermore, prenatal stress may lead to abnormal methylation levels of genes associated with important pathways of embryogenesis in the placenta, possibly affecting fetal development, as well as the peripheral tissues of the mother and baby ( 23 ). Both animal and human studies have confirmed that epigenetic mechanisms are important modulators of the susceptibility of offspring exposed to stressors during pregnancy to chronic diseases, especially metabolic diseases ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…84 Methylation of the BDNF gene also has been detected in the placenta, umbilical cord, and venous blood of women who had suffered traumatic events during pregnancy and in buccal mucosa samples from newborns at 2 months of age (exposed to intrauterine stress). 85 Methyl-CpG-binding protein 2 (MeCP2) interacts with methylated DNA in the brain and inhibits/activates gene transcription. Mutations of MeCP2 and knockout in hypothalamic neurons (e.g., POMC ARC and Sim1) lead to hyperphagia and obesity.…”
Section: Methylationmentioning
confidence: 99%
“…86 The MECP2 gene is involved in the development of MetS, and the MECP2 protein controls body weight through post-translational modifications. 85 It has been found that mice with a MeCP2 muta-tion/deletion have lower levels of BDNF in the brain. At the same time, BDNF is involved in the phosphorylation of MeCP2 (antidepressant effect).…”
Section: Methylationmentioning
confidence: 99%